Harnessing Communityʼs Creative Expression and Indigenous Wisdom to Create Value : Tacit-Implicit-Explicit (TIE) Knowledge Creation Model - Narayanan, A/L N. Kulathu Ramaiyer; Tariq, Zaman; Yeo, Alvin Wee (2011)
Knowledge creation process in indigenous communities is a less focused but important area of research. We proposed the TacitImplicit-Explicit (TIE) model to conceptualize the information and know-how engagement process with indigenous communities. The model is an extension of traditional knowledge creation models. It will provide an insight of the flow and absorption of new information and know-how in indigenous communities and will describe that on the base of new information, how the community flourishes innovation and knowledge creation? A case study of Bario-Buayan community information exchange and knowledge creation is presented while the research is still in progress to collect more case studies from communities and to validate the model.